Analisis Teoritik Kecenderungan Perilaku Delinkuensi Remaja di Sekolah/Madrasah - Syarifan Nurjan; Edy Kurniawan; Azid Syukroni; Maryono Maryono (Universitas Muhammadiyah Ponorogo, 2022)
Adolescent delinquency behavior begins with a transitional period or a transition period from childhood to adulthood, which undergoes various changes, namely biological, cognitive and social. Vulnerable adolescent age; early adolescence at 12-15 years, middle adolescence at 16-18 years, and late adolescence at 19-21 years. Adolescent psychosocial development depends on family, peer, and school contexts that produce identity, independence, friendship, sexuality, and achievement.Adolescent delinquency is bad behavior that is a symptom of illness (pathological) socially caused by social neglect so that adolescents develop a form of deviant behavior. Juvenile delinquency refers to a wide range of socially unacceptable status offenses to criminal acts.Theoretical analysis of juvenile delinquency in schools/madrasahs are (1) the theory of adolescent behavior, (2) the theory of adolescent change, (3) the theory of juvenile delinquency which discusses the forms and factors of juvenile delinquency behavior, (4) meta-analysis of juvenile delinquency behavior, and ( 5) social ties as a factor in juvenile delinquency behavior.